(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Cervical cancer is one of the leading causes of morbidity and mortality amongst the gynaecological cancer in Bangladesh.This study was carried out to assess the knowledge of cervical cancer, awareness of the women towards the cervical cancer screening program and its vaccination in Bangladesh. A cross- sectional interview based study was conducted using a self administered questionnaire between January 1 ,2013 and June 31, 2013 on 508 respondents. Convenience sampling was applied among the women attending at Gynae Out Patient Department (GOPD) of Chittagong Medical College Hospital for VIA (Visual Inspection with Acetic Acid) test. Of the 508 respondents only 211(41.54%) told that they had idea about cervical cancer, while only 114 (22.44%) knew that VIA is the screening test for cervical cancer.A total of 390 (76.77%) respondents did not know any cause of cervical cancer.Most of the respondents (80%) came for VIA due to doctors advice.After doing VIA among 229 respondents, 149 (65.07%) told that they had been counseled for the next follow - up by the health professionals and 118 (51.52%) were ready for routine periodic screening.Majority (85.88%) of the respondents were absolutely ignorant about the vaccine of cervical cancer. Age and marital status did not influence their knowledge but the level of education and occupation was found to positively influence their knowledge of cervical cancer and their acceptance of the screening test.This study highlights that majority of women in Bangladesh are not adequately equipped with knowledge concerning cervical cancer. Adequate health information and counseling on cervical cancer and regular screening test need to be emphasized in our country. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 57-60